2019
DOI: 10.4081/jphr.2019.1533
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Issues in Antibiotic Prescribing in French Nursing Homes: An Ethnographic Study

Abstract: Background:Medication prescription is generally the responsibility of doctors. In nursing homes, the nursing staff is often the first to suspect an infection. Today, physicians are more confident with nursing assessment, relying primarily on nursing staff information. Very few studies have investigated the nurses’ influence on decision of medical prescription. This study investigates the role of nurses in antibiotic prescribing for the treatment of suspected infections in nursing home residents.Design and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Regarding their role in antibiotic prescribing, we found that most nursing home nurses agreed to discuss more with general practitioners about the relevance of prescribing an antibiotic. This result is similar to that reported in a French study conducted by Chaaban et al which showed that nurses were motivated to take part in an educational training program on antibiotic therapy to improve their knowledge and to be able to discuss antibiotic prescriptions with the general practitioner (Chaaban et al, 2019). Even if the responsibility for prescribing antibiotics is clearly assigned to physicians, nursing home nurses could participate in the resident's management by providing useful information or suggesting to delay the prescription and wait a few days to reconsider the need for an antibiotic in case of diagnostic uncertainty, provided that severity criteria are absent (Fleming et al, 2014).…”
Section: Itemssupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding their role in antibiotic prescribing, we found that most nursing home nurses agreed to discuss more with general practitioners about the relevance of prescribing an antibiotic. This result is similar to that reported in a French study conducted by Chaaban et al which showed that nurses were motivated to take part in an educational training program on antibiotic therapy to improve their knowledge and to be able to discuss antibiotic prescriptions with the general practitioner (Chaaban et al, 2019). Even if the responsibility for prescribing antibiotics is clearly assigned to physicians, nursing home nurses could participate in the resident's management by providing useful information or suggesting to delay the prescription and wait a few days to reconsider the need for an antibiotic in case of diagnostic uncertainty, provided that severity criteria are absent (Fleming et al, 2014).…”
Section: Itemssupporting
confidence: 90%
“…Using a structured approach to provide data on residents' clinical assessments to general practitioners can help nurses communicate accurately and help the general practitioners make diagnoses (Baier et al., 2022). They could support general practitioners in their infection management and development of an optimal antibiotic treatment plan (Chaaban et al., 2019) when communication between off‐site physicians and on‐site nurses is harmonious (Gahr et al., 2007). In our study, most nursing home nurses agreed to have the possibility of adapting the antibiotic drug formulation to each resident based on their knowledge of the residents' clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from studies suggest agreement among nurses’ regarding their role in stewardship. 85.3% of nurses perceive themselves as being sources of information for patients regarding antibiotics [ 15 ], and agreed (5-point scales) that their assessment of the patient (M = 3.8), communication with providers (prescribers) (M = 4.1), knowledge of a patients’ baseline (M = 3.8), clinical assessment of a patient and communication with patient and family members (M = 3.8) influenced whether the patient received antibiotics [ 63 ]. However, it is unclear how other RACF staff (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses have been identified as central to GP decision-making about treatment in RACF contexts [ 15 , 52 ]. Role responsibilities include instigating the escalation of care when needed (e.g.…”
Section: Introductionmentioning
confidence: 99%